Transformasi Pendidikan Agama Islam di Era Digital: Perspektif Sosial dan Tantangan Kontemporer - Mufidah Hayati; Firani Putri; Muhammad Hafizh; Januar Januar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Globalization has had a transformational impact on social life in various segments. Open territories between countries by information and communication technology. This has implications for the dimensions of life, especially the existence and projection of Islamic education. Islamic education faces multidimensional and complex challenges such as technology, ideology, social, cultural, economic and political. Other challenges are professionalism, integrity, solidarity and vision. The aim of this research is to analyze Islamic religious education from a social perspective and its challenges today. This research uses a qualitative approach by means of library research, namely collecting research sources from books, journals, proceedings, which are then analyzed and conclusions are drawn. The results of the research show that the solution to education today and in the future is to increase human resources, including the ability to produce people who can contribute to national development, the ability to produce people who can appreciate, enjoy and maintain the results of development, and the ability to give birth to a humanizing process. and humanity is continuously moving towards a nation that is just and wise and virtuous. Islamic education provides an effective and efficient solution in organizing the social life system amidst multidimensional globalization.